Assessment of oxidative stress markers and hearing thresholds in patients with obstructive sleep apnea-hypopnoea treated with cysteine and superoxide dismutase therapy. - Serra, Agostino; Maiolino, Luigi; Cocuzza, Salvatore; Di Luca, Milena; Campione, Gianluca; Licciardello, Luisa; Di Mauro, Paola (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: In OSAHS, the hypoxia and reoxygenation cicles, maintain a state of oxidative stress, which seems to cause a change in the oxidative balance. Our aim is to compare the markers of oxidative stress with audiological findings and OSAHS severity, in OSAHS patients untreated and also treated ones, with cysteine and superoxide dismutase. Methods: 65 patients (42 Men, 23 Women) with 30-65 years age range have been enrolled, with a mean age of 52.6 ± 13.3 years with moderate OSAHS. We have analyzed plasma and lymphocyte markers of oxidative stress (glutathione, thioredoxin and heat shock protein) and they were underwent tonal audiometry. Patients were divided in two groups: Group A (32 patients) included patients treated for 8 weeks with cysteine and superoxide dismutase; Group B (33 patients) included patients untreated. Results: The research showed a significant increase in reduced glutathione levels (p